2005
DOI: 10.1086/430320
|View full text |Cite
|
Sign up to set email alerts
|

Combination of HIV‐1–Specific CD4 Th1 Cell Responses and IgG2 Antibodies Is the Best Predictor for Persistence of Long‐Term Nonprogression

Abstract: HIV-1-specific CD4 Th1 responses combined with IgG2 antibodies and IFN- gamma -producing CD4 Th1 cells are better predictors of long-term nonprogression than are virus parameters, host genes, or HIV-1-specific CD4 Th1 or CD8 T cell proliferation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
92
2
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 106 publications
(102 citation statements)
references
References 60 publications
7
92
2
1
Order By: Relevance
“…Two studies from the same French cohort linked gp41-specific IgG2 and CD4 ϩ Th1 responses with long-term nonprogression (35,36), and Lal et al found an association between the absence of IgG2 antibodies to gp41 and clinical disease (14). These results are consistent with our observation that IgG2 antibodies to gp41 are enriched among ECs with protective HLA alleles.…”
Section: Discussionsupporting
confidence: 92%
“…Two studies from the same French cohort linked gp41-specific IgG2 and CD4 ϩ Th1 responses with long-term nonprogression (35,36), and Lal et al found an association between the absence of IgG2 antibodies to gp41 and clinical disease (14). These results are consistent with our observation that IgG2 antibodies to gp41 are enriched among ECs with protective HLA alleles.…”
Section: Discussionsupporting
confidence: 92%
“…3) (81). The range of HIV DNA levels was smaller than the range of HIV RNA levels, but nonetheless identified several patient subgroups in large cohorts; in particular, LTNPs and elite controllers had significantly lower HIV DNA levels than pro- (61,(88)(89)(90) (Fig. 3).…”
Section: Other Tissues and Fluidsmentioning
confidence: 99%
“…Patients who naturally control HIV infection (long-term nonprogressors and elite controllers) have very low and stable total HIV DNA levels, with median values of 2.3 and 1.5 log 10 copies/ 10 6 PBMC reported in, respectively, 66 and 15 patients (88)(89)(90). Similarly, posttreatment controllers in the VISCONTI cohort, for whom treatment was initiated early during the primary infection and long-term viral control after treatment interruption was maintained, had low total HIV DNA levels (median, 1.71 log 10 copies/10 6 PBMC; 14 patients) (91,92) (Fig.…”
Section: Total Hiv Dna In Blood During Untreated Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relevance for functional CD4+ T-cell help in the maintenance of effective CTL populations has recently also been reported for viral infections other than HIV, including EBV and CMV infections [134,135]. The potential importance of virusspecific T helper cell activity is further highlighted by studies that have associated the presence of gp41-specific antibodies with CD4+ T-cell responses to Gagp24 [136,137]. Regardless of the well-documented anti-viral effects of neutralizing Ab responses [138] general antibody-responses have not emerged as strong markers of HIV control.…”
Section: Hiv Disease Markers Associated With Virus-specific Cellular mentioning
confidence: 92%